Human papillomavirus and oral disease – emerging evidence: a review. (31st January 2013) - Prabhu, SR; Wilson, DF
Abstract: Human papillomavirus (HPV) infections have received considerable attention in recent years. Of the 120 or so known types of the virus, some cause a variety of benign wart‐like lesions of the skin and genital and oral mucosae, whilst others are aetiologically associated with cervical and anogenital cancers. Recent epidemiologic evidence suggests that HPV may also be an independent risk factor for oropharyngeal cancer. In this context it has been suggested that HPV virus may modulate the process of carcinogenesis in some tobacco and alcohol induced oropharyngeal cancers and act as the primary oncogenic agent for inducing carcinogenesis among non‐smokers. Dental practitioners have a major role in detecting all lesions of the oral mucosa caused, or possibly caused, by HPV. This paper briefly reviews the current state of knowledge of molecular and clinical aspects of HPV infections of the oral mucosa.